MENUJU PERTUMBUHAN INDUSTRI HIJAU DI SULAWESI SELATAN - takdir, Takdir (STISIP Widyapuri Mandiri Sukabumi, 2024)
South Sulawesi Province, with the commitment and collaboration of all parties, needs to further optimize the transformation towards green Industriy growth in order to manage natural resources that ensure environmental sustainability and equal livelihoods for all levels of society.The Green Economy Index is a benchmark for evaluating the achievements and effectiveness of Indonesia's Industriy transformation towards a green Industry. The main principle of the Green Economy is to create high Industriy growth, along with encouraging social welfare, maintaining Industriy quality and environmental carrying capacity. The Green Economy Index (GEI) or the Indonesian Green Economy Index consists of 15 indicators which cover three pillars, namely Industriy, social and environment.The policy that needs to be implemented in implementing a green economy in South Sulawesi is controlling land conversion by increasing the capacity of farmers by implementing climate change agriculture technology or climate-smart agriculture. Providing environmental services in the form of assistance or incentives for farmers who cultivate plants by maintaining the sustainability of the carrying capacity of their land or who contribute to improving environmental quality. Development of downstream land-based natural resources using technology that does not harm the environment or surrounding communities and can provide high added product value for farmers. Keywords: Green Industry